The Probe Team [episode no. 314] (Probe Productions, 1994)
The first part is about the job of Guest Relations Officer in nightclubs. The Cultural Center of the Philippines in its 25th birthday has still funding problems and this is shown in the second part of this tape. The lastpart is about Mt. Guiting Guiting in Sibuyan Island.